INGLIZ VA O‘ZBEK ADABIYOTIDA TABIATNING BADIIY TASVIRI - Kulmuhammedova , Lobar Anvarjonova; Bozorboyev , Sirojiddin Anvar o‘g‘li (Educational Research in Universal Sciences, 2023)
In this article, the artistic depiction of nature in English and Uzbek literature is described and compared to each other.